KEBIJAKAN FINANCING TO VALUE, FINANCING TO DEPOSIT RATIO DAN PENGARUHNYA TERHADAP PEMBIAYAAN RUMAH DI JAWA TIMUR TAHUN 2013-2015 - Muhammad Rachmad Hidayat; Sri Herianingrum (Universitas Airlangga, 2018)
The purpose of this research is to analyze the impact of the macroprudential policy that applied in Indonesia (in this case are Financing to Value and Financing to Deposit Ratio) on house financing in East Java.The object of this research are financing to value and financing to deposit ratio, and the subject of this research is house financing in 2013 until 2015. The data of this research are available in the website of the Bank Indonesia. Analysis method that used for this research is the multiple linear regression with 0,05 significationThe result of this research shows if FDR, FTV aqd MMQ-IMBT are affecting partially positive significant to House Financing in East Java. Whilst FTV aqd Murabaha and Istishna’ is affecting partially negative significant to house financing in East Java. Simultaneously, FDR, FTV aqd MMQIMBT and FTV aqd Murabahah and Istishna’ giving significant impact to house financing in EastJava REFERENCESAgung, Juda. 2010. Mengintegrasikan Kebijakan Moneter dan Makroprudensial: Menuju Paradigma Baru Kebijakan Moneter di Indonesia Pasca Krisis Globa;.Working Paper, No. 07. Bank IndonesiaArnold, Bruce, Claudio Borio, Luci Ellis dan Fariborz Moshiran. 2012. Syatemic Risk, Maroprudential Policy Frameworks, Monitoring Financial System, and the Evolution of Capital Adequacy, Journal of Banking and Finance, vol 36: 3125-3132Anshori, Muslich & Sri Iswati. 2009. Metodologi Penelitian Kuantitatif, Surabaya: Airlangga University PressBank of England. 2009. The Role of Macroprudential Policy. A Discussion Paper, November———————-, 2011.Instrument of Macroprudential Policy. A Discussion Paper, DecemberGujarati, Damodar. 1999. Ekonometrika Dasar, Terjemahan Sumarno Zain, Erlangga, JakartaKasmir. 2003. Bank dan Lembaga Keuangan Lainnya. Jakarta : Raja Grafindo PersadaMariza, Princes Dianria. 2015. Analisis Pengaruh Kebijakan Loan to Value, Inflasi, Suku Bunga Kredit, dan Loan to Deposit Ratio terhadap Penyaluran Kredit Pemilikan Rumah Provinsi Lampung Periode 2010;01-2014;09. Lampung : Universitas Lampung Purnawan, Muhammad Edhie dan M. Abd. Nasir. 2015. The Role of Macroprudential Policy to Manage Exchange Rate Volatility, Excess anking Liquidity and Credits. Jakarta : Bank IndonesiaQuint, Dominic dan Pau Rabanal. 2011. Monetary and Macroprudential Policy in an Estimated DSGE Model of Euro Area. 12th Jacques Polak Annual Research Confrence, November.Tim Riset SMF, 2015, Dampak Perubahan Loan to ValueTerhadap Perkembangn Kredit Pemiikan Rumah.Sugiono. 2011. Metode Penelitian Pendekatan Kuantitatif, Kualitatif, dan R&D. Bandung: ALFABETASuryani, 2011, Analisis Pengaruh Financing to Deposit Ratio (FDR) Terhadap Profitabilitas Perbankan Syariah, Lhokseumawe: STAIN Malikussaleh Lhokseumawe.